Exploration of tribological estimation on alumina reinforced polymer mixtures evaluated by ANOVA approach. (2022) - Sathees Kumar, S.; Viswanath Allamraju, K.; Pati, Pravat Ranjan; Kumar Gandla, Praveen
Abstract: This paper reports the arrangement, portrayal and exploratory examination of Nylon 6 (N6) built up with alumina oxide (Al2 O3 ) mixtures. The test samples were ready in an Injection molding machine, by fluctuating the weight extents of Al2 O3 elements mixed with N6. The tribological characteristics of the mixtures were seen by utilizing a nail to plate wear test rig under dry sliding conditions. The significant four boundaries were considered to appraise the wear of the mixture substances like load (P), speed (N), weight % (W), and sliding speed (V) and similar four-cycle boundaries are considered to foster the Numerical models. The mathematical models were created by the procedure of plan of the trial (DOE). ANOVA method was applied to take a look at the legitimacy of the model. Mathematical models were created and the reactions were successfully anticipated. Wear impacts of interaction boundaries on reaction were investigated by plotting outlines.